2017
DOI: 10.14786/flr.v5i4.296
|View full text |Cite
|
Sign up to set email alerts
|

Mood Moderates the Effect of Self-Generation During Learning

Abstract: Generating information, compared to reading, improves learning and enhances long-term retention of the learned content. This so-called generation effect has been demonstrated repeatedly for recall and recognition of single words. However, before adopting generating as a learning strategy in educational contexts, conditions moderating the effect need to be identified. This study investigated the impact of positive and negative mood states on the generation effect with short expository texts. According to the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
8
0
4
Order By: Relevance
“…To roughly summarize the results, the authors observed that learners with a positive emotional state showed better recall performances from self-generated information than learners in a negative emotional state, who profited more from the completely formulated words. Similarly, very recently, Schindler et al (2017) found that learners were better able to remember generated words in a positive compared to a negative emotional state, whereas this was not the case for the recall of completely formulated words. Therefore, it seems that a positive emotional state seems to be more beneficial when an additional learning task requires cognitive flexibility or the generation of new information.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…To roughly summarize the results, the authors observed that learners with a positive emotional state showed better recall performances from self-generated information than learners in a negative emotional state, who profited more from the completely formulated words. Similarly, very recently, Schindler et al (2017) found that learners were better able to remember generated words in a positive compared to a negative emotional state, whereas this was not the case for the recall of completely formulated words. Therefore, it seems that a positive emotional state seems to be more beneficial when an additional learning task requires cognitive flexibility or the generation of new information.…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, it seems that a positive emotional state seems to be more beneficial when an additional learning task requires cognitive flexibility or the generation of new information. If we translate the results of this rather basic research from Fiedler et al (2003) as well as Schindler et al (2017) to our study, we can assume that the beneficial effect of elaborative interrogations compared to text is especially pronounced for learners with a positive emotional design, and only to a lesser extent for learners with a neutral design. This can be supported by the explanation that learners in a positive emotional state may especially show increased motivation to engage in a task if confronted with an SGL activity.…”
Section: Introductionmentioning
confidence: 89%
“…Así mismo, con inducción de estados anímicos positivos y negativos, Kuhbandner y Pekrun (2013) evaluaron el fenómeno de «olvido inducido por la recuperación selectiva» y observaron que dicho efecto era mayor en los participantes de ánimo negativo respecto al control y al ánimo positivo y que estos últimos eran los que mejor recordaban aquello que se le solicitaba en la evaluación final, pero que no había sido solicitado inicialmente. Finalmente, Schindler et al, (2017) indagaron en estudiantes universitarios el efecto de inducir un estado de ánimo positivo o negativo en la recuperación tanto de aspectos literales como de aspectos inferenciales y encontraron que los pacientes con un ánimo positivo inducido se desempeñaron mejor que el resto de los grupos solo en información inferencial.…”
Section: Emoción Y Comprensión Lectoraunclassified
“…Los resultados también son acordes con los obtenidos en investigaciones previas sobre emoción y lectura (Boyle, 1986;Ellis et al, 1995Ellis et al, , 1997Kuhbandner & Pekrun, 2013;Schindler et al, 2017;Tornare et al, 2016), todos vinculados con diseños experimentales diferentes al presente, ya que partieron de modelos discretos. En estos experimentos, se observa que la tristeza se correlaciona con resultados inferiores respecto a la alegría.…”
Section: Discusión Finalunclassified
See 1 more Smart Citation